Penerapan Model Modified Find Someone Who dan Quiz-Quiz Trade untuk Meningkatkan Keterampilan Sosial Siswa Sekolah Dasar - Yenny Fardilla; Budi Eko Soetjipto; I Made Suardana (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: The purpose of this study is to improve social skills of fifth grade students through the application of the Modified Find Someone Who dan Quiz-Quiz Trade Models. This type of research uses a type of classroom action research. The research subjects were fifth grade students at Sumbersari 1 Malang Primary School. Data collection of students social skills using observation and questionnaires. The results of this study indicate that the Modified Find Someone Who and the Quiz-Quiz Trade models can improve students' social skills. This can be proven by the increase in the observation results of the students' social skills in the first cycle reaching 76.2% and the second cycle reaching 84.5%. The results of the students social skills questionnaire in the first cycle reached 81.0% and increased in the second cycle reached 85.2%. Abstrak: Tujuan dari penelitian ini adalah untuk meningkatkan keterampilan sosial siswa kelas V melalui penerapan model Modified Find Someone Who dan Quiz-Quiz Trade. Jenis penelitian ini menggunakan jenis Penelitian Tindakan Kelas. Subjek penelitian adalah siswa kelas V di SDN Sumbersari 1 Malang. Pengumpulan data keterampilan sosial siswa menggunakan observasi dan angket. Hasil penelitian ini menunjukkan bahwa model Modified Find Someone Who dan Quiz-Quiz Trade dapat meningkatkan keterampilan sosial siswa. Hal tersebut dapat dibuktikan dengan meningkatnya hasil observasi keterampilan sosial siswa pada siklus I mencapai 76.2% dan siklus II mencapai 84,5%. Hasil angket keterampilan sosial siswa pada siklus I mencapai 81,0% dan meningkat pada siklus II mencapai 85,2%.